Profil Membaca dan Interaksi Pembaca dengan Buku Teks Siswa Sekolah Dasar - - Suherli (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2007)
Abstract: Information of reading profile and readers’ interaction with text in learning activity can be useful in understanding the factors that influence in determining course text book readability. The purpose of this research is to describe elementary schools’ students reading profile and their interaction with national standarized  course text-books. This research was using descriptive-analytic method. The subjects were elementary school’s students and national standarized  course text-books which were sampled by purposive technique. The results found reading activities and intensities outside learning hour was very view. The quality of text book readability was depend on vocabulary comprehension, students’ intimacy, main point students’ comprehension, the chosen discourse, attraction of the book contents, and easiness of material structure.